Kama Sutra, a Pandora’s Box of Evils? - Sandeep S. Jaiswal, (Indian Journal of Social Science and Literature (IJSSL), 2024)
This paper shows that Kama Sutra, the oldest living literature on sex, love an relationship has a flawed core concept that is neither holistic, moral or uplifting nor balanced and harmonious to human nature. It has some positives in speaking about the truth but it is patchy as most of the verses speak about satisfying a human desire with “just do it” philosophy rather than control your lust to seek pleasure but not at the cost of sacrificing your values. When this Pandora’s box is open it will do more harm than good to society as the fundamental foundation is weak and verses speak from ignorance of real knowledge.